Psychiatric and neurodevelopmental disorders in childhood-onset epilepsy - Berg, Anne T. (2011)
Childhood-onset epilepsy is associated with psychiatric and cognitive difficulties and with poor social outcomes in adulthood. In a prospective cohort of young people with epilepsy, we studied psychiatric and neurodevelopmental disorders (PD and ND) and epilepsy-related characteristics, all factors which may influence long-term social outcomes. 501 subjects, 159 with complicated (IQ<80 or brain lesion) and 342 with uncomplicated epilepsy were included. PD and ND were more common in complicated epilepsy (p<0.005). In uncomplicated epilepsy, externalizing but not internalizing disorders were strongly associated with ND. Internalizing disorders and ND were associated with lack of 5-year remission. Type of epilepsy was not associated with NDs or PDs. Various comorbid conditions in epilepsy cluster together and are modestly associated with imperfect seizure control. These need to be considered together in evaluating and managing young people with epilepsy and may help explain long-term social outcomes above and beyond poor seizure control.